Assessing public opinions on the likelihood and permissibility of gene editing through construal level theory. Issue 4 (2nd October 2021) - So, Derek; Sladek, Robert; Joly, Yann
Abstract : Anticipatory policy for gene editing requires assessing public opinion about this new technology. Although previous surveys have examined respondents' views on the moral acceptability of various hypothetical uses of CRISPR, they have not considered whether these scenarios are perceived as plausible. Research in construal level theory indicates that participants make different moral judgments about scenarios seen as likely or near and those seen as unlikely or distant. Therefore, we surveyed a representative sample of 400 Americans and Canadians about both the likelihood and the permissibility of 23 commonly discussed uses of gene editing. Respondents with more knowledge of gene editing generally thought these applications would be more likely within the next 20 years. There was a strong positive relationship between the perceived likelihood and permissibility of most CRISPR applications. Our results suggest that ongoing public engagement efforts for gene editing could be improved by taking its perceived time-frames into account.